Impact of pattern dependency of SiGe layers grown selectively in source/drain on the performance of 14 nm node FinFETs. (October 2016) - Qin, Changliang; Wang, Guilei; Kolahdouz, M.; Luo, Jun; Yin, Huaxing; Yang, Ping; Li, Junfeng; Zhu, Huilong; Chao, Zhao; Ye, Tianchun; Radamson, Henry H.
Abstract: A complete mapping of 14 nm FinFETs performance over 200 mm wafers was performed and the pattern dependency of SiGe selective growth was calculated using an empirical kinetic molecule model for the reactant precursors. The transistor structures were analyzed by conventional characterization tools and their performance was simulated by considering the process related variations. The applied model presents for the first time a powerful tool for transistor community to predict the SiGe profile and strain modulating over a processed wafer, independent of wafer size.